ANALISIS USAHA PEMANFAATAN KULIT PISANG RAJA FERMENTASI MOL (MIKROORGANISME LOKAL) DIBANDINGKAN Trichoderma harzianum SEBAGAI PAKAN BERBENTUK PELET TERHADAP KELINCI REX JANTAN LEPAS SAPIH - jessica natalina manurung (Jurnal Peternakan Integratif, 2014)
The waste of Banana Peel were used as alternative feed for rabbits. This research was conducted in the laboratory Animal Biology Faculty of Agriculture, University of Sumatera Utara in August to November 2013. This research aimed the economic value of the utilization of  raja banana peel  local microorganisms fermentation compared Trichoderma harzianum of weaning male rex rabbits. The research used twenty one weaning male rex rabbits with initial body weight 732±133 g with used survey method. Treatments were used in this research are Raja Banana Peel without fermentation at the level 45% (P0); Raja Banana Peel fermented by MOL at the level 15% (P1); 30% (P2); 45% (P3) and Raja Banana Peel fermented by Trichoderma harzianum at the level 15% (P4); 30% (P5); 45% (P6). The parameters that used are total cost, total revenue, profit and lost, Revenue cost ratio (R/C ratio) and income over feed cost (IOFC). The result on profit and lost (Rp/head/period) for treatment P0, P1, P2, P3, P4, P5 and P6 were 14.817, 14.811, 17.196, 13.394, 9.319, 4.954 and 4.287. respectively, while for R/C were 1,42, 1,41, 1,48, 1,38, 1,26, 1,14 and 1,12, and for IOFC (Rp/head/period) were 20.070,53, 20.063,72, 22.448,64, 18.647,34, 14.572,59, 10.207,14 and  9.540,38. Treatment fermented by MOL and  Trichoderma harzianum decreased profit, R/C ratio and income over feed cost (IOFC). The conclusion of this research is that the utilization of  Raja Banana Peel without fermented level 45% is efficient for rex rabbits diet. Keywords : Business analysis, Raja banana peel fermentation, Rex rabbits, Profit and lost, R/C ratio